Research Innovation in Building the Spirit of Islamic Educational Leadership in the MTs Aisyiah Binjai Environment - Khairuddin, Ahmad; Tanjung, Alfian; Piliang, Fenny Mustika (Lembaga Riset Mutiara Akbar, 2024)
Building the Spirit of Islamic Leadership in the MTs Aisyiah Binjai Environment. This research aims to find out, analyze the general description of students at MTs Aisyiah Binjai and foster leadership in students within the MTs Aisyiah Binjai environment. This type of research is a qualitative method. The research location was carried out in the MTs Aisyiah Binjai environment. Determining informants as selected data sources using purposive sampling techniques. Data collection uses observation techniques, questionnaires, interviews and documentation. Data validity is obtained through credibility, transferability, dependability, and confirmatory. Qualitative data analysis: reduction, data exposure, and drawing conclusions. The results of the research show a lack of interest among students in participating in extracurricular activities at MTs Aisyiah Binjai. Data obtained by researchers through direct interviews with respondents shows that most students only focus on education, namely learning in class. Meanwhile, they have very little interest in doing activities outside the classroom. There are several ways that can be done to cultivate a leadership spirit, including building knowledge, reading diligently; open the windows of your own cells; self-discipline; work with priorities; do or delegate; build trust and respect; maintain emotional stability; train yourself to communicate and be competent; learn to write; and use management. In cultivating a leadership spirit in students, there are three important points, namely leadership, team working and communication. Meanwhile, to be a superior leader, you must have vision, value and courage. Vision, value, courage, competence, strong and natural character which is supported by three skills that must be possessed, namely academic technical skills or knowledge, human skills or skills, and spiritual skills. and religious.